MONITORING OF HYGIENIC STATUS OF RAW MILK MARKETED IN LAHORE CITY, PAKISTAN - K. Muhammad; I. Altaf; A. Hanif; A. A. Anjum; M. Y. Tipu (Journal of Animal and Plant Sciences, 2009)
Milk is an important source of nutrition and its hygienic quality is important from public health point of view. The quality of the milk was assessed by monitoring aerobic viable bacterial count, coliform count and methylene blue reduction (MBR) test. Milk is procured from rural or suburban areas, transported at ambient temperature to different marketing points of Lahore city and sold as loose raw milk to consumers. The milk samples collected from these marketing points of Gulberg, Iqbal, Ravi and Gunj Bukish towns, contained 8.5+0.6, 7.5+0.83, 5.4+1.6 and 5.1+1.7 counts (Log10) of aerobic viable bacteria, respectively. It indicated that milk samples from Gulberg (100%), Iqbal (100%), Ravi (60%) and Gunj Bukish (53%) Towns contained the bacterial counts beyond the acceptable limits (106/ ml), respectively. There was no linear correlation between aerobic bacterial count and coliform count in samples collected from either of the towns. However, coliform count was higher than log 107.6+1.7 in the milk samples collected from either of the towns. Although, there was no correlation between results of total aerobic bacterial count and that of MBR test in the market samples but higher dilution was having lower MBR time of the same sample. This is why negative correlation between aerobic bacterial count and MBR is still reliable and valid test for monitoring hygienic status of market milk.
Keywords: Methylene blue reduction test; Coliform count; Aerobic bacterial count; Raw milk